2020
DOI: 10.37231/ajmb.2020.4.2.354
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia-Related Knowledge Amongst Pregnant Women in Kuala Terengganu, Malaysia.

Abstract: The prevalence of anaemia amongst pregnant women in developing countries is increasing yearly, particularly in Malaysia. This problem may be due to their lack of knowledge of anaemia and food choice. This study aimed to measure the knowledge levels on anaemia and iron absorption amongst pregnant women in Kuala Terengganu, as well as the association of knowledge levels between socio-demographic characteristics. Pregnant women were selected from government health clinics located in Kuala Terengganu, Malaysia. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…Pregnant women whose husbands have no formal/primary education and those whose husbands have middle/JHS level of education were less likely to have adequate knowledge of iron nutrition and supplementation than those whose husbands have secondary/higher education. This finding is contrary to Hasnah, et al (2020) who studied anaemia-related knowledge among pregnant women in Kuala Terengganu, Malaysia and found no association between anaemia-related knowledge among pregnant women and their husbands' level of education. This finding may be because pregnant women whose husbands have no formal/primary education may be less informed about their health and adverse pregnancy outcomes by their low-educated husbands compared to those whose husbands have higher education (Habib, Zein-Alabdin, Alenazy & Nooh, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Pregnant women whose husbands have no formal/primary education and those whose husbands have middle/JHS level of education were less likely to have adequate knowledge of iron nutrition and supplementation than those whose husbands have secondary/higher education. This finding is contrary to Hasnah, et al (2020) who studied anaemia-related knowledge among pregnant women in Kuala Terengganu, Malaysia and found no association between anaemia-related knowledge among pregnant women and their husbands' level of education. This finding may be because pregnant women whose husbands have no formal/primary education may be less informed about their health and adverse pregnancy outcomes by their low-educated husbands compared to those whose husbands have higher education (Habib, Zein-Alabdin, Alenazy & Nooh, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…While overweight and obesity are the key risk factors for many chronic diseases, such as cardiovascular diseases, diabetes, and certain cancers (3), iron deficiency or hypoferremia is the most prevalent single micronutrient deficiency globally (4). Untreated iron deficiency can cause iron deficiency anemia, a severe health problem that appears in the form of tiredness, reduced life productivity, and poor maternal health, especially among pregnant women (5)(6)(7)(8). Growing evidence supports the existence of an association between obesity and iron deficiency (9).…”
Section: Introductionmentioning
confidence: 99%
“…5 Findings of the study are consistent with a study from Malaysia which reported that anemia is more common among women which may be due to lack of knowledge regarding anemia. 10 Similarly, another study from Saudi Arabia Tabuk noted that majority of the women have poor knowledge and attitude towards anemia. 11 Likewise, another study from Bangladesh found that knolwdge of pregnant women regarding anemia and inaqdeuate iron intake is the main cause of anemia during pregnancy.…”
Section: Discussionmentioning
confidence: 98%